2:08 Normal School Steam Plant - Unknown (publisher not identified, 1897)
Not the side of the Normal School building usually photographed, this view is of the power plant and smoke stack, restrooms, and other out-buildings at the rear (south side) of the main building (later renamed Baldwin Hall).